2019
DOI: 10.1038/s41440-019-0270-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dosage-escalation of low-dosage esaxerenone added to a RAS inhibitor in hypertensive patients with type 2 diabetes and albuminuria: a single-arm, open-label study

Abstract: The stimulation of mineralocorticoid receptors is linked to the development of hypertension and cardiovascular or renal damage in patients with diabetes, and the blockade of these receptors may be an effective treatment option. This open-label study with a 12-week treatment period assessed the antihypertensive (primary) and antialbuminuric (secondary) efficacy and safety of esaxerenone as an add-on therapy to a renin-angiotensin system inhibitor in hypertensive patients with type 2 diabetes and albuminuria (ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
55
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 48 publications
14
55
2
Order By: Relevance
“…In our study, the extent of reductions in eGFR during treatment of PA with esaxerenone was similar to that seen with other MR blockers, indicating that correction of hyperfiltration probably contributed to the observed reduction in eGFR, which may indicate recovery of the tubuloglomerular feedback damaged by hyperaldosteronism [38]. Given that eGFR tended to return to baseline levels after the end of esaxerenone treatment in other studies [30,39], the eGFR reductions in this study are considered to be caused by hemodynamic changes rather than organic renal damage.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In our study, the extent of reductions in eGFR during treatment of PA with esaxerenone was similar to that seen with other MR blockers, indicating that correction of hyperfiltration probably contributed to the observed reduction in eGFR, which may indicate recovery of the tubuloglomerular feedback damaged by hyperaldosteronism [38]. Given that eGFR tended to return to baseline levels after the end of esaxerenone treatment in other studies [30,39], the eGFR reductions in this study are considered to be caused by hemodynamic changes rather than organic renal damage.…”
Section: Discussionsupporting
confidence: 86%
“…The phase 3 study [29] also showed that esaxerenone 2.5 mg/day was noninferior to eplerenone 50 mg/day and that esaxerenone at 5 mg/day exhibited superior BP-lowering effects over esaxerenone at 2.5 mg/day. In a study of esaxerenone in patients with moderate renal dysfunction with diabetes with albuminuria [30], incremental dose escalation starting from a low dose was able to manage serum K + elevations and renal function safely while exerting antihypertensive effects. Data from these studies provide important guidance regarding the role of esaxerenone in the management of hypertension with related comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…Significant reductions in the UACR were observed even when esaxerenone was added to a RAS inhibitor, consistent with clinical studies on type 2 diabetes that demonstrated a dose-dependent reduction in the UACR [24,25]. However, Adverse events (n ≥2 in either study) eGFR estimated glomerular filtration rate a In monotherapy, two patients discontinued due to adverse events, one experienced altered consciousness and the other had chest pain, and the first event was judged to be related to the study drug.…”
Section: Discussionsupporting
confidence: 83%
“…Esaxerenone has demonstrated good antihypertensive activity in a variety of patients, including those with uncomplicated grade I-III hypertension, hypertension with moderate renal impairment, hypertension with type 2 diabetes mellitus with albuminuria, and hypertension associated with primary aldosteronism (Daiichi Sankyo Co., Ltd., unpublished data, J305 and J307 studies; and published data [25][26][27][28]). The currently available clinical study data are summarized in Table 1.…”
Section: Introductionmentioning
confidence: 99%
“…The antihypertensive effects of esaxerenone persisted throughout 52 weeks of treatment even when used as a monotherapy or when it was administered as an add-on therapy with reninangiotensin system (RAS) inhibitors or calcium channel blockers (CCBs) [27]. In addition to its antihypertensive effects in hypertensive patients with type 2 diabetes and albuminuria, renoprotective effects have also been reported, with the urinary albumin/creatinine ratio decreasing by 32.4% from baseline during treatment with 5 mg/day esaxerenone, even in the presence of RAS inhibitors [26]. Similar antihypertensive and renoprotective effects have been observed in patients with moderate kidney dysfunction (Daiichi Sankyo Co., Ltd., unpublished data, J305 study).…”
Section: Introductionmentioning
confidence: 99%